Seed treatment with micronutrients on yield and grain quality of rice - Filho, Morel Pereira Barbosa; Fageria, Nand Kumar; Fonseca, Jaime Roberto (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out to study the effect of seed treatment with the micronutrients Cu, Zn, Mo and B on different plant characteristics and yield of vice (Oryza sativa L.) cv. IAC 47. The plant height of Zn treated seeds was significantly increased compared with untreated seeds. The yield, yield components and rice quality were not affected by the treatments. However, seed treatment with water alone or with Zn increased grain yield.